Collective Food Security under the Framework of the ASEAN Community: A Reflection from Indonesia’s Food Policy - Gautama Budi Arundhati; Muhammad Bahrul Ulum; Rosita Indrayati (PADJADJARAN Jurnal Ilmu Hukum (Journal of Law), 2019)
AbstractSince its inception in 1967, the Association of Southeast Asian Nations (ASEAN) has been based upon the common interests of its member states and the principle of solidarity. These two cornerstones have played an important role in the efforts for development of this regional organization. Under the principle of solidarity, ASEAN configures a distinct intergovernmentalism subjected to collective decision-making which emphasizes common understanding, including on how it approaches security concerns. This article aims to discuss and analyze the prospect of the collective food security in ASEAN by taking into account the legal frameworks of food security in the ASEAN community and Indonesia. Specifically, this article reflects the development of ASEAN and the member states’ common problem of providing food for national consumption. ASEAN’s development shows that it has committed to food security. For instance, ASEAN signed the Agreement on the ASEAN Food Security Reserve. However, this institution has not paid enough significant attention to food security and the ASEAN integration pillars are often justified to exempt food security amongst its priorities. Therefore, this article clarifies that food security is an essential part of the pillars. By the inclusion of food security to such pillars and taking account of Indonesia’s experiences, there is an importance for ASEAN to re-consider food security. This consideration is not only to achieve part of its ultimate objectives to bring prosperity but also to ensure regional stability.Ketahanan Pangan Kolektif dalam Kerangka Komunitas ASEAN: Sebuah Refleksi dari Kebijakan Pangan IndonesiaAbstrakSejak didirikan pada 1967, Association of Southeast Asian Nations (ASEAN) berlandaskan pada kepentingan bersama para negara anggota dan prinsip solidaritas. Kedua landasan utama ini memainkan peran penting dalam upaya pembangunan organisasi regional ini. Berdasarkan pada prinsip solidaritas, ASEAN membentuk sebuah kelembagaan intergovernmental yang berbeda dengan keputusan kolektif yang menekankan pada pemahaman bersama, termasuk dalam kaitannya bagaimana organisasi ini menyikapi urusan ketahanan. Artikel ini bertujuan untuk mendiskusikan dan menganalisis prospek ketahanan pangan kolektif di ASEAN dengan mempertimbangkan kerangka hukum ketahanan pangan di komunitas ASEAN dan Indonesia. Artikel ini secara spesifik merefleksikan perkembangan ASEAN dan permasalahan bersama pada negara-negara anggotanya dalam penyediaan pangan untuk memenuhi konsumsi nasional. Perkembangan ASEAN menunjukkan bahwa terdapat komitmen mengenai ketahanan pangan. Misalnya, ASEAN telah melakukan penandatanganan Perjanjian Cadangan Ketahanan Pangan ASEAN. Namun, institusi ini tidak begitu menunjukkan keseriusan terhadap ketahanan pangan dan pilar-pilar integrasi ASEAN seringkali dijustifikasi untuk mengecualikan ketahanan pangan dalam ke dalam daftar prioritas. Oleh karena itu, artikel ini mengklarifikasi bahwa ketahanan pangan sebenarnya sudah tercakup di dalam pilar-pilar tersebut. Dengan dimasukkannya ketahanan pangan dan belajar dari pengalaman Indonesia, ASEAN perlu mempertimbangkan kembali pentingnya ketahanan pangan. Atas pertimbangan tersebut, hal ini dimaksudkan dalam rangka mencapai bagian dari tujuan utama ASEAN yang tidak hanya untuk mewujudkan kesejahteraan tetapi juga memastikan stabilitas regional.DOI: https://doi.org/10.22304/pjih.v6n1.a1